Simple Technology of Material Physics of Groundwater Conservation in Dealing with Climate Change in Disaster Areas of North Sumatera - Dayana*, Indri; Satria, Habib; Fauzi, Muhammad; Rahwanto, Adi; Rianna, Martha (Aceh International Journal of Science and Technology, 2023)
Water is a natural resource with a very important function for human life and advancing general welfare, so water is the basic capital and the main development factor. After the eruption in the Mount Sinabung area, the supply of healthy water was inadequate both in quantity and quality, even though the Karo Regency government made efforts to provide this healthy water. For this reason, appropriate technology is needed in post-eruption water treatment in Mount Sinabung to become healthy water and be used by the local community. This research aims to provide information about Groundwater Conservation Technology in Facing Climate Change in the Disaster Areas of North Sumatra. The method used is quantitative with a purposive sampling technique by selecting 6 wells from 348 wells around Mount Sinabung. Chemical parameters for sampling each - each 1 liter of water to be put in bottles previously cleaned and rinsed with distilled water first, then dried. Laboratory Tests then examined them. There is a simple technology in the form of a water filter made from a mixture of sand, activated carbon, and dried starfruit leaves, which can neutralize contamination of substances such as sulfur and others in the water to obtain healthy water suitable for people in the disaster area.